Is Toxoplasma gondii Infection a Cause or a Coincidence in an Adolescent with Psychosis? - Yucel, Hüsniye; Acikel, Burak; Nur Öz, F; Senel, Saliha (Journal of Pediatric Infectious Diseases, 2020)
Although presumed to be relatively harmless in immunocompetent patients, toxoplasmosis has been linked to several psychiatric problems such as schizophrenia, bipolar disorder, and suicidal/aggressive behaviors. We describe an 11-year-old young adolescent girl with psychoses who was ultimately diagnosed with toxoplasmosis. It is an unusual presentation of Toxoplasma gondii infection that adds new knowledge to the current level of literature about the substantial role of Toxoplasma gondii in the etiology of neuropsychiatric diseases. We propose that screening for toxoplasmosis is needed besides other etiologies in differential diagnosis of psychiatric symptoms particularly in endemic areas.
Keywords: Toxoplasma gondii; toxoplasmosis; psychosis; hallucinations; adolescent